Investment in blood the real cost of Britain's Afghan War - Ledwidge, Frank (Yale University Press, 2013)
In this follow-up to his much-praised book Losing Small Wars: British Military Failure in Iraq and Afghanistan, Frank Ledwidge argues that Britain has paid a heavy cost - both financially and in human terms - for its involvement in the Afghanistan war. Ledwidge calculates the high price paid by British soldiers and their families, taxpayers in the United Kingdom, and, most importantly, Afghan citizens, highlighting the thousands of deaths and injuries, the enormous amount of money spent bolstering a corrupt Afghan government, and the long-term damage done to the British military's international reputation. In this hard-hitting exposé, based on interviews, rigorous on-the-ground research, and official information obtained through the Freedom of Information Act, Ledwidge demonstrates the folly of Britain's extended participation in an unwinnable war. Arguing that the only true beneficiaries of the conflict are development consultants, international arms dealers, and Afghan drug kingpins, he provides a powerful, eye-opening, and often heartbreaking account of military adventurism gone horribly wrong.